2003
DOI: 10.1007/s10295-003-0071-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of the pectinolytic enzyme in the lactic acid fermentation of potato pulp by Rhizopus oryzae

Abstract: Rhizopus oryzae strain NBRC 4707 produced lactic acid and ethanol more efficiently than strain NRRL 395 in potato pulp, an agricultural by-product of the starch industry. The two strains developed comparable activities of xylanase, cellulase, alpha-amylase, and glucoamylase, while the polygalacturonase activity of strain NBRC 4707 was double that of strain NRRL 395. The addition of commercial pectinase enhanced the formation of metabolites, suggesting that the degradation of pectic substances determines the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…However, in the present study, although the weight was not significantly improved, the feed conversation efficiency was improved in the FCJP group compared to control. The pectin content of Citrus junos might be influenced by the probiotic organisms and activate to generate pectinolytic enzymes resulting in higher production of lactic acid bacteria [36,43,44]; where lactic acid bacteria can complement with the other beneficial microbes can exhibit synergism to utilize the feed with higher efficiency in broiler [45]. Therefore, combination of flavonoids, naringin, hesperidin, carotinoids, polyphenols, and flavonols, pectins, punicalagin, flavonoids, peduculagin, ellagitannin, and punicalin, some other phenolic compounds with the microbial generated organic compounds [34][35][36], the feed efficiency was improved in the FCJP2 group.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, although the weight was not significantly improved, the feed conversation efficiency was improved in the FCJP group compared to control. The pectin content of Citrus junos might be influenced by the probiotic organisms and activate to generate pectinolytic enzymes resulting in higher production of lactic acid bacteria [36,43,44]; where lactic acid bacteria can complement with the other beneficial microbes can exhibit synergism to utilize the feed with higher efficiency in broiler [45]. Therefore, combination of flavonoids, naringin, hesperidin, carotinoids, polyphenols, and flavonols, pectins, punicalagin, flavonoids, peduculagin, ellagitannin, and punicalin, some other phenolic compounds with the microbial generated organic compounds [34][35][36], the feed efficiency was improved in the FCJP2 group.…”
Section: Discussionmentioning
confidence: 99%
“…oryzae NBRC 4707, caused the potato pulp to ferment rapidly and formed high amounts of lactic acid and ethanol, and that, as a result, the preservation and flavor were improved (Oda et al, 2002;Saito et al, 2003). In this study, to develop a low-cost fiber rich bread, the use of this FPP in bread-making was examined.…”
Section: Introductionmentioning
confidence: 99%
“…However, though this potato pulp is used in part as compost and organic fertilizer in Japan, it is not sufficiently utilized. The main reasons seem to be as follows: (1) if left untreated, spoilage is very fast; and (2) when utilized for food, the quality of the food is significantly reduced (Mayer and Hillebrandt, 1997).Therefore, to develop the utility of this potato pulp for various food, we examined its treatment with various microorganisms and found that a filamentous fungus, R.oryzae NBRC 4707, caused the potato pulp to ferment rapidly and formed high amounts of lactic acid and ethanol, and that, as a result, the preservation and flavor were improved (Oda et al, 2002;Saito et al, 2003). In this study, to develop a low-cost fiber rich bread, the use of this FPP in bread-making was examined.…”
mentioning
confidence: 99%
“…Its fermentation by R. olyzae is governed by the degradation of pectic substances that bind independent cells in the potato tuber (Saito et a/., 2003). When the fungal cells were grown on fruit peels containing high amounts of pectin, polygalacturonase activity increased enough to enhance the formation of lactic acid and ethanol in potato 225 pulp (Saito et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…All of these strains synthesize malic and fumaric acids and are included exclusively in a group differing from the strains accumulating lactic acid (Oda et al, 2003). Recently, sequences of 18S-28S rRNA spacer regions were shown to be identical to lactic acid-accumulating strains of R. olyzae and Amy'lomyces rouxii but not to strains of R. olyzae that produce mallc and fumaric acids (Abe et a/., 2003).…”
mentioning
confidence: 99%